The Implementation of Sustainable Development Goals (SDGs) at PT. Golden Energy Mines Tbk. - Widyasari, Della; Bayangkara, Ida Bagus Ketut (Universitas Bhayangkara Surabaya, 2025)
Sustainable Development Goals (SDGs) is a global development agenda that encourages the involvement of all sectors, including mining companies, in achieving sustainable development. This study aims to analyze the SDGs implementation strategy at PT Golden Energy Mines Tbk (GEMS), a coal mining company in Indonesia. The method used is a descriptive qualitative approach with literature study techniques and company policy analysis. The results of the analysis show that PT GEMS has integrated the principles of SDGs into its operational activities and business strategies, especially in the environmental, social and governance (ESG) aspects. The company has implemented corporate social responsibility (CSR), energy efficiency, post-mining reclamation, and community engagement programs as part of its commitment to the SDGs. However, challenges in the form of policy harmonization, sustainability reporting, and strengthening cross-stakeholder collaboration still need to be addressed to ensure more effective implementation of the SDGs and long-term impact.